The Effect of Principal Managerial Competency and Learning Digitalization Program on Achieving Graduate Competency Standards at SMA Negeri 05 Makassar - Fina Fina; Baharuddin Baharuddin; Mardhiah Mardhiah (Journal of Pedagogi, 2024)
Principals must possess managerial competence to effectively manage education. The learning digitalization program provides tools and resources that enhance the learning experience, broaden access, and increase interactivity, contributing to learners' understanding and skill development. Both managerial competence and learning digitalization contribute to improved teacher performance, learning outcomes, and the overall quality of education, enabling students to achieve the established graduate competency standards. This study aims to: 1) analyze the effect of the principal's managerial competence on achieving graduate competency standards at SMA Negeri 05 Makassar; 2) analyze the impact of the learning digitalization program on the achievement of graduate competency standards at SMA Negeri 05 Makassar; and 3) examine the combined effect of the principal's managerial competence and the learning digitalization program on the achievement of graduate competency standards at SMA Negeri 05 Makassar. This quantitative ex post facto research uses a managerial approach. The sample size consisted of 306 respondents, selected through a stratified random sampling technique. Data were collected using a questionnaire and analyzed through descriptive and inferential statistics, employing simple and multiple linear regression analysis. The results indicate that: 1) the principal's managerial competence influences the achievement of graduate competency standards by 29.3%; 2) the learning digitalization program affects the achievement of graduate competency standards by 15.8%; and 3) both the principal's managerial competence and the learning digitalization program together have a positive and significant impact on achieving graduate competency standards by 34.8%.